2021
DOI: 10.20885/ajim.vol3.iss1.art4
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian young consumers’ intention to donate using sharia fintech

Abstract: Purpose: This research examines the effect of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), religiosity, and company image on intention to use Sharia fintech for donation among Indonesian young consumers. Methodology: This study used a quantitative method with data collection techniques using an online questionnaire. Respondents filled out the questionnaire based on the Likert scale from 1 (strongly disagree) to 4 (strongly agree). The questionnaire was distributed and collected in less than one we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…Even though the donation applications of non-religious philanthropic institutions may be not very user-friendly, donors can overcome it with their digital intelligence. This confirms the studies by Rohmah et al (2020) finding that ease of donating using fintech crowdfunding has no significant effect on interest in paying ZIS, and that of Agustiningsih et al (2021) indicating that ease of use does not affect users' intention to use fintech to pay donations.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Even though the donation applications of non-religious philanthropic institutions may be not very user-friendly, donors can overcome it with their digital intelligence. This confirms the studies by Rohmah et al (2020) finding that ease of donating using fintech crowdfunding has no significant effect on interest in paying ZIS, and that of Agustiningsih et al (2021) indicating that ease of use does not affect users' intention to use fintech to pay donations.…”
Section: Resultssupporting
confidence: 88%
“…Religion also motivates giving because it enhances conviction (it shapes people's opinions about what is right and wrong, and hence people have a more significant concern for other people's wellbeing) and instills a sense of community and social context in which people are more aware of opportunities to give (Jamal et al, 2019). The results of this study are in line with the research of Rohmah et al (2020), who stated that partially the ease of donating using fintech crowdfunding has no significant effect and has a negative relationship to interest in paying ZIS, and also Agustiningsih et al (2021)'s study finding that ease of use does not affect users' intention to use fintech to pay donations. Likewise, Won-jun & Lee (2018) found that convenience did not significantly affect the intention to use financial technology.…”
Section: Resultssupporting
confidence: 88%
“…Participating in waqf is one of the noble acts of helping others, as well as fulfilling religious teaching and receiving blessings from Allah. Muslims with a high level of religiosity will also have social willingness, as reflected in the activity of making donations (Agustiningsih et al, 2021).…”
Section: Trust In the Indonesian Waqf Board And Waqf Institutions And...mentioning
confidence: 99%
“…DD also owns a musical content in DD TV YouTube to entertain its viewers called "Insan Muda", an epithet for DD's youth-segmented members. (Agustiningsih et al, 2021). DD's contents also own emotional appeals which can motivate donors to donate.…”
Section: Marketing Communicationmentioning
confidence: 99%